2005
DOI: 10.1103/physrevb.71.184422
|View full text |Cite
|
Sign up to set email alerts
|

Gradual transition from insulator to semimetal ofCa1xEuxB6with increasing Eu concentration

Abstract: The local environment of Eu 2+ ͑4f 7 , S =7/2͒ in Ca 1−x Eu x B 6 ͑0.003ഛ x ഛ 1.00͒ is investigated by means of electron spin resonance ͑ESR͒. For x Շ 0.003 the spectra show resolved fine and hyperfine structures due to the cubic crystal electric field and nuclear hyperfine field, respectively. The resonances have Lorentzian line shape, indicating an insulating environment for the Eu 2+ ions. For 0.003Շ x Շ 0.07, as x increases, the ESR lines broaden due to local distortions caused by the Eu/ Ca ions substitut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Electron microscopy data indicate the coexistence of insulating Ca-rich and metallic Eu-rich regions that percolate at x ≈ 0.30 [17]. Moreover, Urbano et al [18] recently analyzed the behavior of the Eu 2+ electron spin resonance (ESR) linewidth and concluded that the percolation of the impurity bound states has already started at x ≈ 0.15, i.e., involving next to nearest neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…Electron microscopy data indicate the coexistence of insulating Ca-rich and metallic Eu-rich regions that percolate at x ≈ 0.30 [17]. Moreover, Urbano et al [18] recently analyzed the behavior of the Eu 2+ electron spin resonance (ESR) linewidth and concluded that the percolation of the impurity bound states has already started at x ≈ 0.15, i.e., involving next to nearest neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…23,[29][30][31] Therefore, there is a disagreement with the positive value for b 4 reported by Luft et al, 32 in La 1−x Gd x B 6 . Using our method of calculation, including the exchange narrowing mechanism, we have reanalyzed their data for the angular dependence of the resonance ⌬H pp ͑ , T͒ and shift, ␦H͑ , T͒, and we obtained ͗b 4 ͘ =−6͑2͒ Oe and 2 b 4 =6͑2͒ Oe for La 1−x Gd x B 6 .…”
Section: +mentioning
confidence: 79%
“…17,[22][23][24][25] In this work, we report electron spin resonance ͑ESR͒ experiments of Eu 2+ ͑S ground state͒ ions diluted in the metallic hexaboride of LaB 6 . It is generally observed that for Eu 2+ and Gd 3+ ions diluted in any cubic metallic/ semimetallic/semiconducting/insulating hosts, the fourth order CFP, b 4 , for both ions, is either positive [26][27][28] or negative, 23,[29][30][31] with different absolute values but always with the same sign. It is then expected that the CF acts in the same manner on the S ground state of Eu 2+ and Gd 3+ ͑4f 7 ; S =7/2͒ ions in LaB 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In this regime the fine and hyperfine structures can no longer be resolved. For Eu 2+ and x ≤ 0.60, the g-value and line width are T-independent down to ~20-30 K [23,24]. The absence, or negligible, T-dependence for these parameters assure us, within the experimental error, that above ~30 K there is no direct or indirect magnetic interaction between the R ions in these systems.…”
Section: +mentioning
confidence: 79%
“…Preliminary X-band data in some of these samples were already presented previously [22] and a complete set of data for the case of Eu 2+ was reported in Ref. [23]. For EuB 6 (x = 1.00) Urbano et al [24] have recently attributed the broad line width observed in their ESR experiments to a spin-flip scattering relaxation process due to the exchange interaction between the Eu 2+ 4f 7 and conduction electrons.…”
Section: Originalmentioning
confidence: 85%